Critical care teaching and medical ethics caring for the unconscious and the critically III - Delilkan, Alex (Penerbit Universiti Teknologi Mara, 2012)
This book represents a compilation of talks, papers and articles; written and published in local journal, news periodicals or presented at scientific conferences and meetings. The compilation has been blended with scripting from previous publications to fit in as a teaching manual.